2019
DOI: 10.1039/c9ra04638k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical research on a new corrosion inhibitor for effective oil and gas acidification

Abstract: A new dibenzylamine-quinoline derivative (DEEQ) was synthesized and shown to be an effective corrosion inhibitor for mild steel in 15% HCl solution for oil and gas acidification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…When the polarization potential continues to increase, it can be observed that the curves are close to coinciding. This is likely due to the rapid dissolution of MS at the strong polarization potential, causing the desorption of NC from the metal surface 53 , 54 .…”
Section: Resultsmentioning
confidence: 99%
“…When the polarization potential continues to increase, it can be observed that the curves are close to coinciding. This is likely due to the rapid dissolution of MS at the strong polarization potential, causing the desorption of NC from the metal surface 53 , 54 .…”
Section: Resultsmentioning
confidence: 99%
“…This approach also gives information on the adsorption of inhibitors on metal surfaces, as has previously been reported for other coatings. 72 Figure 8 shows representative contact angle measurements in which both the droplet and its reflection on the substrate are presented.…”
Section: Orgmentioning
confidence: 99%
“…When the polarization potential continues to increase, it can be observed that the curves are close to coinciding. This is likely due to the rapid dissolution of mild steel at the strong polarization potential, causing the desorption of inhibitors from the metal surface 39 .…”
Section: Adsorption Isotherm and Thermodynamic Parametersmentioning
confidence: 99%